2018
DOI: 10.1002/aic.16192
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on gas hydrate formation and slurry viscosity in the presence of wax crystals

Abstract: Clarifying the interaction effect between hydrate and wax is of great significance to guarantee operation safety in deep water petroleum fields. Experiments in a high-pressure hydrate slurry rheological measurement system were carried out to investigate hydrate formation and slurry viscosity in the presence of wax crystals. Results indicate that the presence of wax crystals can prolong hydrate nucleation induction time, and its influence on hydrate growth depends on multiple factors. Higher stirring rate can o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 76 publications
(128 reference statements)
1
48
0
Order By: Relevance
“…Up to now, many studies have been conducted to investigate the interaction between hydrate and wax in terms of nucleation, formation, agglomeration, , deposition, , and plugging . The details and main conclusions of these studies have been discussed in our previous study and will not be repeated here.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, many studies have been conducted to investigate the interaction between hydrate and wax in terms of nucleation, formation, agglomeration, , deposition, , and plugging . The details and main conclusions of these studies have been discussed in our previous study and will not be repeated here.…”
Section: Introductionmentioning
confidence: 99%
“…To date, different research has been performed to study the coupling between hydrate issues and wax issues. The results of this research haves shown that wax could affect hydrate issues through affecting the nucleation, formation, agglomeration, , deposition, , and plugging processes. However, the main conclusions and mechanisms obtained from this research can be quite different and sometimes contradictory with each other.…”
Section: Introductionmentioning
confidence: 84%
“…Hydrate nucleation induction time versus wax content at different stirring rates under the initial pressure of 7.0 MPa. [Adapted with permission from ref . Copyright 2017, Wiley.…”
Section: Characteristics Of Wax-hydrate Deposition In Oil–gas–water T...mentioning
confidence: 99%
“…Meanwhile, the effect of wax on hydrate formation rate and aggregation between hydrate particles was studied. In addition, Chen et al 142 and Shi et al 143 also studied the influence of the wax crystals on the induction period of hydrate formation, and they believed that wax crystals would extend the induction period, which is not conducive to the hydrate formation, as shown in Figure 4.…”
mentioning
confidence: 99%